Extraperitoneal Colonic Sutures - Blanco, Edgardo; Benedetti, Mario; Zubillaga, Dante; Pomatta, José; Viotti, Rolando; Bianchi, Ana (Cirugía del Uruguay, 1979)
Experimental evaluation of colonic sutures in extraperitoneal site, using 30 dogs on whom colonic suture is brought out through subcutaneous cellular !ayer.